Phylogenetic relationships of the genera of Ptiloneuridae (Psocodea, ‘Psocoptera’, Epipsocetae) and a test on the monophyly of Brasineura Silva-Neto & García Aldrete and Loneuroides García Aldrete - Silva-Neto, Alberto Moreira Da; Aldrete, Alfonso N. García; Rafael, José Albertino (Zootaxa, 2016)
The phylogenetic relationships of the genera of Ptiloneuridae were inferred on the basis of morphological characters of adult specimens. Two distinct clades are recognized: one, including Belicania, Euplocania, Omilneura, Perucania, Timnewia and Triplocania, and the other, including Brasineura, Loneura, Loneuroides, Ptiloneura, Ptiloneuropsis and Willreevesia. Brasineura and Loneuroides are recognized as monophyletic. A correction of nomenclature for the parts of the phallosome in Brasineura was made; we also modified the identification key to the genera of Ptiloneuridae, in the couplets that separate Loneura from Brasineura.